Innovations in bulk photovoltaics: design strategies for boosted photocurrent - Akhil Sreevalsan; Hyosung Choi (Light: Science & Applications)
Abstract The limitations imposed by low contact resistance, restricted polarization access, and tensile strain in bulk photovoltaic systems were mitigated by the engineering and optimization of edge semimetal contacts using Bi/Au. Improved bulk PV photocurrent and intriguing prospective applications are made possible by this effort.